2019
DOI: 10.1002/ejhf.1423
|View full text |Cite
|
Sign up to set email alerts
|

High risk of heart failure associated with desmoglein‐2 mutations compared to plakophilin‐2 mutations in arrhythmogenic right ventricular cardiomyopathy/dysplasia

Abstract: Background Previous studies suggested that genetic status affects the clinical course of arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) patients. The aim of this study was to compare the outcome of desmoglein‐2 (DSG2) mutation carriers to those who carry the plakophilin‐2 (PKP2) mutation, the most common ARVC/D‐associated gene. Methods and results Consecutive ARVC/D patients carrying a pathogenic mutation in PKP2 or DSG2 were selected from a national ARVC/D registry. The cumulative freedom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 34 publications
1
45
1
Order By: Relevance
“…Data by Hermida et al are different from those published by the US–The Netherlands and Italy study groups, who failed to determine HF correlation with the genetic status. Variable prevalence of PKP2 vs. DSP or DSG2 mutation carriers in different study populations, referral bias, variable cohort size and follow‐up period might be some of the reasons explaining the differences in the published series.…”
Section: Fundingcontrasting
confidence: 59%
See 2 more Smart Citations
“…Data by Hermida et al are different from those published by the US–The Netherlands and Italy study groups, who failed to determine HF correlation with the genetic status. Variable prevalence of PKP2 vs. DSP or DSG2 mutation carriers in different study populations, referral bias, variable cohort size and follow‐up period might be some of the reasons explaining the differences in the published series.…”
Section: Fundingcontrasting
confidence: 59%
“…A recent study on a DSG2 founder mutation demonstrated that homozygote DSG2 patients exhibited full disease penetrance, though clinical presentation varied from HF to late‐onset symptoms . Similarly, Hermida and colleagues confirmed the prognostic value of a more complex genetic status in determining end‐stage HF (either death or transplantation) independent of a DSG2 mutation presence, reflecting a variable inheritance disease pattern …”
Section: Fundingmentioning
confidence: 90%
See 1 more Smart Citation
“…Genetic status affects the clinical course of patients with arrhythmogenic right ventricular cardiomyopathy/dysplasia. Hermida et al . compared the outcomes of desmoglein‐2 (DSG2) mutation carriers to those with plakophilin‐2 (PKP2) mutation.…”
Section: Geneticsmentioning
confidence: 99%
“…During a median follow‐up of 5.6 years, DSG2 and PKP2 mutation carriers had a similar risk of sustained ventricular arrhythmia, but DSG2 mutation carriers were at higher risk of transplantation/heart failure (HF)‐related death. Thus, DSG2 mutation is associated with a high risk of end‐stage HF, compared to PKP2 mutation, and careful haemodynamic monitoring is needed in these patients …”
Section: Geneticsmentioning
confidence: 99%